Kerugian BBM Akibat Kemacetan Di Kota Bandar Lampung (Studi Kasus Pada Ruas Jalan Pangeran Antasari) - walimuda, hilda trianda; Putra, Sasana; Sulistyorini, Rahayu; Herianto, Dwi (Universitas Lampung, 2022)
AbstractBandar Lampung City is the third largest and most populous city on Sumatra Island with a population of 1,033,803 people (BPS, 2018). Due to the large population, traffic jams often occur, one of which is on Jalan Pangeran Antasari. The road is a City Street class which has a length of 5.6 km and a width of 15 m.Methods Data collection is carried out during peak hours, namely in the morning at 07.30 - 09.00 WIB and during busy afternoons at 16.15 - 17.45 WIB on weekdays, namely Tuesday and Friday. The method used is a moving car observer. The data collected is data on density, speed and fuel demand. The calculation results are obtained from type I vehicles, namely vehicles with a capacity of 1469 cc for liters of gasoline which are widely used during trips in the afternoon, namely 0.46 liters of gasoline with the largest average density of 67.28 pcu/km. From type II vehicles, which are vehicles with a capacity of 2000 cc for liters of gasoline which are widely used for travel, namely 0.7 liters with a density of 90.99 pcu/km in the afternoon hours. Of the two types of vehicles in this study, the consumption of liters of gasoline is greater, that is, it occurs in type II vehicles with a capacity of 2000 cc compared to type I vehicles with a capacity of 1496 cc. The greater the density value, the more gasoline is used.Keywords: BBM, Congestion, Jalan Pangeran Antasari.